A systematic literature review about dimensioning safety stock under uncertainties and risks in the procurement process. (2021) - Barros, Júlio; Cortez, Paulo; Carvalho, M. Sameiro
Abstract: This paper analyses literature contributions in the search for safety stock problem under uncertainties and risks in the procurement process, focusing on the dimensioning problem (determination of the safety stock level). We perform a systematic literature review (SLR) from 1995 to 2019 in relevant journals, covering 193 selected articles. These selected articles were classified into three safety stock main issues: safety stock dimensioning, safety stock management, and safety stock positioning, allocation or placement. The SLR analysis allowed the identification of literature gaps and research opportunities, thus providing a road map to guide future research on this topic. Highlights: A review on safety stock problem under uncertainties and risks in the procurement process is conducted. Articles were classified into safety stock dimensioning, management, and placement. There are no existence of surveys/reviews that cover all safety stock issues. Literature gaps were identified, allowing to disclose future research opportunities.